2022
DOI: 10.1039/d2nj02553a
|View full text |Cite
|
Sign up to set email alerts
|

Photostabilization of ketoprofen by inclusion in glycyrrhizin micelles and gel nanoparticles

Abstract: Ketoprofen (KP) is known to be the most photosensitive among the nonsteroidal anti-inflammatory drugs and may induce phototoxic and photoallergic reactions. Phototoxic side effects of KP are associated with the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The formation of these species was proved by chemical nuclear polarization in addition to other methods [ 72 , 73 ]. Selyutina et al [ 74 ] attempted to use glycyrrhizin to increase the photostability of KP. To study the photolysis of ketoprofen in micelles and gel nanoparticles of GA, they also used CIDNP and NMR.…”
Section: Self-associates Of Glycyrrhizin and Inclusion Complexes Wi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of these species was proved by chemical nuclear polarization in addition to other methods [ 72 , 73 ]. Selyutina et al [ 74 ] attempted to use glycyrrhizin to increase the photostability of KP. To study the photolysis of ketoprofen in micelles and gel nanoparticles of GA, they also used CIDNP and NMR.…”
Section: Self-associates Of Glycyrrhizin and Inclusion Complexes Wi...mentioning
confidence: 99%
“…The antioxidant activity of GA was also studied by CIDNP technique [ 74 , 95 ], which is one of the most informative experimental methods for studying free radical reactions in complex chemical and biochemical processes [ 96 98 ]. The authors traced the effect of GA on the behavior of paramagnetic species formed during UV irradiation of xenobiotics, including drug molecules (naproxen and ketoprofen), and found that the concentration of free radicals in solutions decreased in the presence of GA [ 74 , 95 ]. In addition, it was reliably established by CIDNP method that the GA molecule captures the solvated electron generated by UV irradiation of naproxen and ketoprofen.…”
Section: Interaction Of Glycyrrhizin With Free Radicals and Solvate...mentioning
confidence: 99%